Responses in metabolic rate to changes in temperature in diapausing Colorado potato beetle Leptinotarsa decemlineata from three European populations. (6th April 2015) - Lehmann, Philipp; Piiroinen, Saija; Lyytinen, Anne; Lindström, Leena
Abstract Many insects survive adverse periods in seasonal environments by entering diapause, a deep resting stage, during which energy consumption is typically low and gas exchange is in the form of a discontinuous gas exchange cycle (DGC). Because insects in high‐latitude environments are severely time constrained during summer, an effective diapause termination with careful regulation of metabolic rate is important. The present study examines whether diapausing Colorado potato beetles Leptinotarsa decemlineata Say originating from three latitudinally different regions in Europe differ in their quantitative or qualitative gas exchange patterns in response to an increasing temperature. Overall production of gaseous CO2, as well as qualitative patterns relating to the DGC, are measured at a late stage of diapause at four different temperatures in increasing order from 13, 18, 23 to 28 °C. Overall CO2 production is found to be lower in the two northern populations (61°49′N and 55°75′N) compared with the southernmost population (45°48′N) but increases as a function of temperature in all populations in a similar way. However, in the northern populations, raising the temperature increases the amount of CO2 discharged during single DGC peaks, whereas the DGC frequency remains relatively unchanged. By contrast, in the southernmost population, the amount of CO2 discharged during individual DGC peaks remains relatively unchanged, whereas the DGC frequency increases as a function of temperature. The observed differences may relate to water retention benefits or, alternatively, energetic benefits relating to heightened gas exchange efficiency in hypoxic or hypercapnic environments. Overall, the results suggest that, although populations of L. decemlineata may have similar thermal sensitivities, they have different qualitative strategies to regulate metabolic re‐activation at diapause termination.